LINGUVOCULTROLOGICAL CHARACTERISTICS OF GENUINE TRANSLATION IN ENGLISH AND UZBEK LANGUAGE TRANSLATORS - Sharipov, Abdulaziz (Журнал иностранных языков и лингвистики, 2021)
In this article, it is important for tourist centers to have a high level of knowledge, with a special focus on history, geography, art and architecture, economics, politics, religion and sociology, and to constantly improve their knowledge and professional skills, culture and speech. One of the important factors is that the guide-interpreters are humane, know the technology of information selection and have the ability to work successfully with foreign and domestic tourists in their best activities.